2022
DOI: 10.1002/acr.24459
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Outcomes for Axial Spondyloarthritis and Sensitivity to Change: A Five‐Year Analysis of the DESIR Cohort

Abstract: Objective To compare the sensitivity to change of different imaging scoring methods in patients with early axial spondyloarthritis (SpA). Methods Patients from the Devenir des Spondylarthropathies Indifferérenciées Récentes (DESIR) cohort fulfilling the Assessment of SpondyloArthritis international Society criteria for axial SpA were included. Radiographs and magnetic resonance imaging (MRI) of the sacroiliac (SI) joints and spine were obtained at baseline, 1, 2, and 5 years. Each image was scored by 2 or 3 re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…We took advantage of the same large national observational cohort of patients with axSpA and a similar methodology that enabled us to demonstrate deceleration of spinal radiographic progression in r-axSpA previously,24 while spinal progression in nr-axSpA was too limited to enable any inhibition to be identified 9. From the different definitions of progression that have been described for the mNY grading system,6–8 we have chosen the one that proved to be the most sensitive to change8 21: worsening of ≥1 grade in ≥1 SIJ and ignoring a change from 0 to 1 over 2 years. Moreover, progression between nr-axSpA and r-axSpA during a 2-year interval is low,7 and the existing cut-off differentiating them proved of limited benefit to predict important outcomes in a recent analysis of our cohort 22…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We took advantage of the same large national observational cohort of patients with axSpA and a similar methodology that enabled us to demonstrate deceleration of spinal radiographic progression in r-axSpA previously,24 while spinal progression in nr-axSpA was too limited to enable any inhibition to be identified 9. From the different definitions of progression that have been described for the mNY grading system,6–8 we have chosen the one that proved to be the most sensitive to change8 21: worsening of ≥1 grade in ≥1 SIJ and ignoring a change from 0 to 1 over 2 years. Moreover, progression between nr-axSpA and r-axSpA during a 2-year interval is low,7 and the existing cut-off differentiating them proved of limited benefit to predict important outcomes in a recent analysis of our cohort 22…”
Section: Discussionmentioning
confidence: 99%
“…Second, we have recently shown that the cut-off of SIJ scoring differentiating between nr-axSpA and r-axSpA seems suboptimal to predict clinically relevant outcomes 22. Finally, as already mentioned, sensitivity to change of progression between disease states is much lower than for the outcome chosen 8 21…”
Section: Methodsmentioning
confidence: 95%
See 1 more Smart Citation
“…Taking into account the evaluation of structural damage, fatty lesions detected on MRI of SIJ had a significantly higher sensitivity to change than pelvic radiographs. Interestingly, this difference was not confirmed for the evaluation of structural changes at spinal level, where MRI was not superior to radiography (42).…”
Section: Imagingmentioning
confidence: 92%
“…Imaging is an essential resource in the diagnosis, as the detection of radiographic sacroiliitis or of active inflammation of SIJ at MRI represents a criterion for classification of axSpA [24]. Moreover, it allows to monitor inflammation and structural damage [31]. Nonetheless, earlier and finer recognition of changes in disease course is needed, preferably with markers that reflect MRI inflammation in the spine [32].…”
Section: Currently Available Biomarkers In As and Psamentioning
confidence: 99%